Freezing of gait and dementia in parkinsonism: A retrospective case–control study. Issue 6 (9th May 2019) - Palermo, Giovanni; Frosini, Daniela; Corsi, Andrea; Giuntini, Martina; Mazzucchi, Sonia; Del Prete, Eleonora; Bonuccelli, Ubaldo; Ceravolo, Roberto
Abstract: Objectives: To support the cognitive model of Freezing of Gait (FoG) we investigated FoG in a cohort of patients with Dementia with Lewy Bodies (DLB). Materials and Methods: We assessed FoG frequency in 19 DLB patients compared to 19 control PD patients within 2 years from symptom onset and with at least 5 years follow‐up. The two groups were matched by age and motor presentation at onset, severity of parkinsonism and disease duration. The presence and severity of FoG was identified as those with a score of 1 or greater on subitem 14 of the Unified Parkinson's Disease Rating Scale Part II (UPDRS II). Results: At T0, 68.4% DLB and 10.5% PD patients experienced FoG ≥1. The prevalence of FoG increased with disease progression (94.7% DLB and 47.3% PD subjects had FoG ≥1 at T5). DLB also showed a more severe FoG (FoG ≥2) than PD (21% vs. 0% at T0 and 52.6% vs. 10.5% at T5), consistently with previous studies reporting FoG prevalence in DLB. Conclusion: This is the first study looking specifically at FoG in DLB, identifying it as a frequent and early feature of DLB and emphasizing the crucial role of cognitive impairment in the occurrence of this mysterious phenomenon. Abstract : FoG frequency was assessed in 19 DLB patients compared to 19 control matched PD patients. At the first examination (T0), 68.4% DLB and 10.5% PD patients experienced FoG. The prevalence of FoG increased with disease progression. DLB also showed a more severe FoG than PD (21% at T0 and 52.6% vs. 10.5% at T5), consistently with previous studies reporting FoG prevalence in DLB. This is the first study looking specifically at FoG in DLB, identifying it as a frequent and early feature of DLB and emphasizing the crucial role of cognitive impairment in the occurrence of this mysterious phenomenon.